Pengaruh Dosage Duration dan Press Station Down terhadap Cacat Unmolded Produk Shoulder Extrusion Tube pada Proses Compression Moulding - Rizki Ahmat Yunifianto; Elka Faizal (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the plastic molding industry, there is a compression molding process to make shoulder tubes for cosmetic products. This research was to determine the effect of dosage duration and press station down parameters on unmolded defects in shoulder extrusion tube products. This research method uses quantitative with an experimental approach. This method is carried out by varying parameter setting dosage duration of 0.25s, 0.30s, 0.35s and press station down of 4 bar, 5 bar, 6 bar. The result od the study found that the parameters of dosage duration, press station down and the interaction of the two variables have a significant effect on unmolded defects. The higher the dosage duration and press station down, the unmolded defects decrease as indicated by the average product weight meeting the standard. The lower two parameters, the more unmolded defects occur, indicating that the average product weight not meet the standard weight tolerance of good products.